Dexrazoxane (Savene) is the standard therapy for anthracycline extravasation Dexrazoxan (Savene) als Standard in der Therapie von Anthrazyklinparavasaten - Mundhenke, Christoph (Chirurgische Praxis, 2010)
Numerous cytotoxic substances show serious tissue damage when extravasation occurs. Especially anthracyclines can cause severe and progressive tissue damage, which rapidly develops after extravasation. In two prospective clinical trials the topoisomerase Il inhibitor dexrazoxane (Savene) proved to be protective against tissue damage after anthracycline extravasation. Therefore dexrazoxane should be the standard therapy after anthracycline extravasation. Chemotherapy units should have dexrazoxane available for emergency application.
CRIS-Team Scopus Importer:2022-11-17
Keywords: Anthracycline; Dexrazoxane; Extravasation; Tissue damage